Scalable Synthesis of Acridinium Catalysts for Photoredox Deuterations - Zilate, Bouthayna; Fischer, Christian; Schneider, Lukas; Sparr, Christof (Synthesis, 2019)
The continuous development of photocatalytic methods incentivizes the design of organic catalysts to complement the frequently used and precious polypyridyl transition metal systems. Herein, a scalable synthesis of suitable acridinium dyes and their application in photoredox deuterations are described. The acridinium catalysts, prepared on multi-gram scale, allowed the deuteration of a pharmaceutically relevant scaffold in high yield and selectivity under mild conditions.
Keywords: acridinium salts; deuteration; Grignard reactions; photoredox catalysis; scalability